Central Mali: Cattle husbandry in the agropastoral system - Wilson, R.T. (1986)
Describes cattle husbandry in the agropastoral system of central Mali, discussing data on the management systems and ownership patterns, herd demography, and productivity including reproductive performance, growth, weight, traction and meat and milk production.